Stenotrophomonas maltophilia – A Threatening Nosocomial Pathogen - Ruchita Gawande; Suvarna Sande (Journal of the Scientific Society)
Stenotrophomonas maltophilia is a ubiquitous Gram-negative rod which has emerged as one of the major causes of nosocomial infections. It can cause pneumonia, septicemia, meningitis, urinary tract, and wound infections, and is associated with high mortality in immune-compromised patients. Pathogenesis in S. maltophilia infections is an outcome of multiple virulence factors, including outer membrane lipopolysaccharide, extracellular enzymes, porins, pilli, biofilm formation, motility, and small colony variants, among others. S. maltophilia shows high intrinsic and acquired resistance to all commonly used antibiotics, limiting the number of therapeutic choices. The aim of this review is to summarize the virulence factors, antibiotic resistance mechanisms, diagnosis, and treatment of S. maltophilia infections.